Konsep Memory Systems dalam Iklan ‘Diskon Ramadhan’ - Elsye Rumondang Damanik (Bina Nusantara University, 2011)
The purpose of the article is to discuss and reminiscence the concept of memory systems and its purpose of marketing activity. Information-processed activity related to marketing activity made this concept is important to be discussed. To limit the problem discussion scope, the article will only discuss about human role asconsumer in marketing activity and also the effects of memory system in helping human being to precede information related to marketing. In presenting the article, the writer had gathered data dan information through literature study from books and information from mass media. The result is that is it important for marketers to understand information-processed stages by their consumers and how the seller optimize or perhaps manipulate the stages to win the market.